Early Childhood Reading Skills through BACERYAH Media at Anak Sholeh Kindergarten: Kemampuan Mengaji Anak Usia Dini melalui Media BACERYAH di TK Anak Sholeh - Zughfalia, Chofsoh Lailin; Salim, Agus (Indonesian Journal of Education Methods Development, 2025)
General Background: Religious education plays a crucial role in early childhood development, fostering foundational skills in Islamic learning. Specific Background: One essential skill is the ability to recite and recognize hijaiyyah letters, including their pronunciation, symbols, and harakat, which for children aged 5–6 years remains at the introductory stage. Knowledge Gap: Conventional methods for teaching hijaiyyah often lack engaging and interactive elements, and limited studies have explored the structured use of tactile media for this age group in a formal early childhood setting. Aims: This study aims to improve the recitation skills of children aged 5–6 years through the use of smart hijaiyyah block media (BACERYAH) at TK Anak Sholeh, Magersari. Results: Using a classroom action research design based on the Kemmis and McTaggart model, involving 12 children, the study recorded an increase in average achievement from 49% (pre-cycle) to 71% (Cycle I) and 83% (Cycle II). Novelty: This research introduces BACERYAH as a structured, multisensory learning tool that integrates visual, tactile, and repetitive practice in early Islamic literacy. Implications: Findings highlight BACERYAH’s potential as an effective medium for supporting early Quranic literacy, offering educators an engaging approach to strengthen foundational religious education in early childhood settings. Highlights: Integration of religious education in early childhood learning Use of BACERYAH as an interactive hijaiyyah learning tool Significant improvement in children’s recitation skills Keywords: Baceryah, Hijaiyyah Letters, Early Childhood Education, Quranic Literacy, Classroom Action Research